Anti-Plaque and Anti-Gingivitis Efficacy of 0.25% Lemongrass Oil and 0.2% Chlorhexidine Mouthwash in Children - Akula S; Nagarathna J; S K Srinath (Tehran University of Medical Sciences, 2021)
Objectives: Research is ongoing to find safe and effective oral hygiene aids for oral self‑care in children. Mouthwashes are used to complete the process of mechanical plaque control. Lack of affordability and side effects of most commercially available mouthwashes limit their use in children. Hence, the cost-effective and easily available essential oil, lemongrass oil, when formulated as a mouthwash, may possibly serve as an adjunct to oral hygiene maintenance. The main objective of this study was to compare the efficacy of lemongrass oil and chlorhexidine (CHX) mouthwash in children. Materials and Methods: Sixty healthy children between 9-12 years were selected. During the initial visit, the plaque pH, plaque index (PI), and gingival index (GI) were assessed, and oral prophylaxis was performed. The patients were randomized into three groups (n=20) and received 0.25% lemongrass oil mouthwash (group A), 0.2% CHX mouthwash (group B), and oral prophylaxis alone (group C). The patients were recalled after 14 and 21 days. ANOVA with post-hoc Bonferroni and paired t-test were used to analyze the results by SPSS software. Results: Intragroup comparison of PI and GI showed a significant decrease between 14 and 21 days in groups A and B (P≤0.05). Intragroup comparison of the mean plaque pH in group A showed a significant increase at day 21 compared with baseline (P=0.028). Conclusion: The results showed that the lemongrass oil mouthwash was effective in reducing PI and GI in children. Thus, it may be used as a good herbal alternative to CHX mouthwash.